The Seller's Sense: Buying–Selling Perspective Affects the Sensitivity to Expected Value Differences. (20th January 2016) - Yechiam, Eldad; Abofol, Taher; Pachur, Thorsten
Abstract: Previous work comparing pricing decisions by buyers and sellers has primarily focused on the endowment effect, the phenomenon that selling prices exceed buying prices. Here, we examine whether pricing decisions by buyers and sellers also vary in sensitivity to differences between objects' expected values (EVs). Both a loss‐aversion account (which posits that losses are weighted more heavily than gains) and a loss‐attention account (which posits increased attention to a task when it involves possible losses) predict that pricing decisions by sellers should exhibit higher sensitivity. The latter, however, additionally predicts that this pattern should only emerge under certain conditions. In studies 1 and 2, we reanalyzed two published datasets in which participants priced monetary lotteries as sellers or buyers. It emerged that sellers showed greater EV sensitivity (defined as the rank correlation between the set price for each lottery and its EV) except in a condition with an extended deliberation time of 15 seconds. In study 3, the buyer–seller difference in EV sensitivity was replicated even when the pricing task was presented repeatedly, while in study 4, it was eliminated when buying and selling trials were randomly mixed. The reduction of the "seller's sense" in long deliberation and mixed trials settings supports an attentional resource‐based account of the differences between sellers and buyers in their EV sensitivity. Copyright © 2016 John Wiley & Sons, Ltd.